Feasibility of optical coherence tomography for the evaluation of Barrett's mucosa buried underneath esophageal squamous epithelium. Issue 4 (4th March 2016) - Hatta, Waku; Uno, Kaname; Koike, Tomoyuki; Ara, Nobuyuki; Asano, Naoki; Iijima, Katsunori; Imatani, Akira; Fujishima, Fumiyoshi; Shimosegawa, Tooru
Abstract : Background and Aim: Evaluation of Barrett's glands buried underneath esophageal squamous epithelium becomes increasingly important in order to achieve curative treatment. However, clinically available endoscopes have critical limitations in depicting subsurface structure, resulting in non‐curative treatment. Optical coherence tomography (OCT) can achieve a high‐resolution cross‐sectional image, equivalent to an optical biopsy. We aimed to assess the feasibility of in vivo use of probe‐type OCT imaging to evaluate Barrett's mucosa buried underneath esophageal squamous epithelium. Methods: From 2008 to 2014 we conducted a single‐center prospective study with 14 consecutive patients with Barrett's adenocarcinoma. Enrolled patients were examined by a probe‐type OCT in vivo, followed by en‐bloc endoscopic submucosal dissection (ESD) with electric marking. Then, one‐to‐one correlations between the OCT images of the buried mucosa and their histological assessment were examined. Results: Overall accuracy, sensitivity, specificity, positive predictive value and negative predictive value of the buried mucosa in the OCT imaging were 85.7% (12/14), 77.8% (7/9), 100% (5/5), 100% (7/7), and 71.4% (5/7), respectively. However, OCT could not easily distinguish non‐dysplastic glands from dysplastic glands. Additionally, the linear distance from the histological squamocolumnar junction in correct cases tended to be longer than that in incorrect cases (mm, median [range]: 2.0 [0.7–7.5] vs 0.5 [0.5–0.5]). Conclusion: We demonstrated, for the first time, that preoperative OCT imaging might be feasible for detecting oral‐side extension of buried Barrett's mucosa in order to remove the entire area with malignant potential by ESD.